2016
DOI: 10.4103/0253-7613.186199
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis reduces the function and expression of α1D-adrenoceptor in superior mesenteric artery of Capra hircus

Abstract: Objective:The objective of this study was to characterize the α1-adrenoceptor (α1-AR) subtypes and evaluate the effect of acidosis on α1-AR function and expression in goat superior mesenteric artery (GSMA).Materials and Methods:GSMA rings were mounted in a thermostatically controlled (37.0°C ± 0.5°C) organ bath containing 20 ml of modified Krebs-Henseleit solution, maintained at pHo of 7.4, 6.8, 6.0, 5.5, 5.0, and 4.5. Noradrenaline (NA)- and phenylephrine (PE)-induced contractile response was elicited in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The SMA was selected as an ex vivo acidosis model for study of vasomotor changes in small ruminants at molecular and functional levels. Previous studies from our laboratory have reported an attenuated vasocontractile response under acidosis (Mohanty et al, 2016). Therefore, it was considered important to examine the effect of acidosis on mediators of vasorelaxation in the SMA.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…The SMA was selected as an ex vivo acidosis model for study of vasomotor changes in small ruminants at molecular and functional levels. Previous studies from our laboratory have reported an attenuated vasocontractile response under acidosis (Mohanty et al, 2016). Therefore, it was considered important to examine the effect of acidosis on mediators of vasorelaxation in the SMA.…”
Section: Introductionmentioning
confidence: 80%
“…The arterial rings of 1.5–2 mm were then mounted between two fine stainless steel L-shaped hooks and kept under a resting tension of 1.5 g in a thermostatically controlled (37.0±0.5°C) 20 ml organ bath containing MKHS continuously aerated with Carbogen. Isometric contraction studies were performed as described previously with minor modifications (Anderson et al, 2014; Dash and Parija, 2013; Mohanty et al, 2016; Singh et al, 2016; Sharma et al, 2017). Briefly, the arterial rings were equilibrated for 90 min before recording of muscle tension, washed every 15 min (using MKHS freshly adjusted to pH 7.4 or 6.8) and the experiment repeated for both endothelium intact (ED+) and denuded (ED-) vessels wherever necessary.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we summarized in Aim 1, previous studies consistently show evidence of adrenergic receptor expression within the fetoplacental vasculature (Fig. 3), suggesting that agonist-activated adrenergic receptor pathways may alter vascular tone in the fetoplacental circulation [40,44,48,49,52,55–83].…”
Section: Methodsmentioning
confidence: 52%